PAMAM-calix-dendrimers: Synthesis and Thiacalixarene Conformation Effect on DNA Binding - Olga Mostovaya (MDPI AG, 2021)
A convenient method for the synthesis of the first generation PAMAM dendrimers based on the thiacalix[4]arene has been developed for the first time. Three new PAMAM-calix-dendrimers with the macrocyclic core in cone, partial cone, and 1,3-alternate conformations were obtained with high yields. The interaction of the obtained compounds with salmon sperm DNA resulted in the formation of the associates of the size up to 200 nm, as shown by the UV-Vis spectroscopy, DLS, and TEM. It was demonstrated by the CD method that the structure of the DNA did not undergo significant changes upon binding. The PAMAM-calix-dendrimer based on the macrocycle in cone conformation stabilized DNA and prevented its degradation.